From Regionalism to Transregionalism: Some Theoretical Conseptualisation of a New Reality - Kseniia A. Efremova (Сравнительная политика, 2017)
Regionalism as an international phenomenon dates back to post-WWII decades. It is well studied both in theoretical and practical perspective. It is quite clear to most researchers what the “old” or “new” regionalism is, and what kind of logic stands behind it. However, the classic theory of regionalism does not explain contemporary processes of interregional and transregional integration, which we witness today. A common point of the three approaches (namely, regionalism, interregionalism and transregionalism) is that all of them are related to globalization. Each of these approaches constitutes a response to globalisation’s challenges, which varies from region to region. Nevertheless, their aims and scope differ greatly. Regionalism represents interstate and transnational co-operation within an international region. It is derived from the logic of institutionalized interactions that may take a range of forms—from regular consultations on the ministerial level to creation of supranational bodies and common policies. Interregional co-operation implies institutionalized agreements between states representing two or more regions, which can act either on their own (i.e. quasi-interregionalism, or hybrid interregionalism) or as a part of a regional organization / informal regional group of states. The logic of interregionalism dwells on the wish for widening the geographic scope of economic interaction by opening new regional markets. Transregional cooperation, on the contrary, is promoted primarily by political factors, such as the wish of some states, which share common values, to unite their efforts in order to play a greater role in global governance. It is argued that the study of regionalism, interregionalism and transregionalism can make an essential contribution to the development of the contemporary theory of international relations.